VALIDASI LEMBAR KAJI JADWAL PEMBELAJARAN DAN BEBAN BELAJAR PESERTA DIDIK DI FAKULTAS ILMU KEPERAWATAN - Karolina Tupen; Samuel M. Simanjuntak (Jurnal Skolastik Keperawatan, 2020)
Evaluation of the learning process can shape the learning experience of students. This study introduces the validation process of a design measuring instrument aspects of the learning experience process experienced by nursing students. Methods: This study is a validation study tool which is carried out using the descriptive correlation method. The population that is the target of this research is 70 students from semester 4 to semester 8 who are registered as regular students in the Undergraduate Nursing Study Program. Samples were recruited accidentally, namely among the student population who were working on class schedules which were later obtained by 39 respondents. Results: The design of the study sheet learning schedule and learning load for nursing students in a good category, namely the coefficient value α = 0.927 with p value <0.05. Conclusion: The reliability value of the review sheet is in good category. Discussion: Continuous or periodic measurement is needed as an effort to improve the learning experience process of nursing students in nursing education institutions in Indonesia. Keywords: Evaluation tool, Course load, Scheduling, Nursing students, Validation